Mensuração da pressão de dióxido de carbono arterial e expirado em lactentes e crianças sob ventilação mecânica invasiva - Rasera, Carmen Caroline (2010)
In neonates and pediatrics patients in intensive care units, monitoring of carbon dioxide has great clinical significance during the invasive mechanical ventilation in the adjustment of ventilatory parameters and detection of complications related to ventilation. The objective of this research is to investigate the correlation and level of agreement between end-tidal carbon dioxide pressure (PetCO2) and the partial pressure of arterial carbon dioxide (PaCO2) in patients in the postoperative period of cardiac surgery, verifying the relationship between both methods in two groups according to body temperature and pulmonary complications. Altogether 74 patients were arranged in the group 1 with 110 measurements of PetCO2, PaCO2 measured at 37 ºC and corrected to the real body temperature of the patient. For the whole sample, the correlation was statistically more significant with corrected PaCO2 (r = 0.92) than with the measured (r = 0.78), throughout the study period. The mean difference between measured PaCO2 and PetCO2 was 4.42 mmHg and increased significantly during body temperature instability, while for corrected PaCO2 the mean difference was 1.12 mmHg and remained low even during hypo or hyperthermia. The results for 246 PetCO2 and PaCO2 pairs analyzed in 42 patients ventilated according to group 2, proved that both methods were highly correlated (r = 0.94) and kept elevated even in patients with respiratory complications. The mean difference between the measurements of both methods was -0.71 mmHg and the values of PetCO2 were within 2 mmHg of PaCO2 in 80.49% of the measurements, indicating a high relationship. The results of this study demonstrate that PetCO2 measured by capnometer is as accurate as PaCO2 measured by arterial blood gases, thus the capnometry can be considered an indirect and noninvasive monitoring method of PaCO2 in patients of intensive therapy under mechanical ventilation.